Mobile-Based Oral Health Self-Screening and Education Application for Pregnant Women - Riolina, Ana; Yulian, Vinami; Sukin, Sukin; Alma Raudhia, Syafira; Syifa Tifani, Amara; Aqila Majid, Alya; Nada Putri, Dhiya; Aisyah, Miranda (Jurnal Kesehatan Gigi, 2025)
Low utilization of dental services among pregnant women, ranging from 35.5% to 49%, is often caused by barriers such as cost, limited awareness, myths about oral health during pregnancy, and fears regarding dental treatment’s impact on the fetus. Local data from the prenatal class and dental clinic at Puskesmas Baki, Gedongan, Sukoharjo, indicate similarly low rates of dental check-ups. This study aimed to develop and evaluate the ‘Ibu Peri Cerita’ mobile application as a tool for self-screening and improving oral health knowledge during pregnancy. A pre-post test design was used with an experimental sample of 23 pregnant women, who were first asked to answer ten oral health knowledge questions.. Participants then used the application to perform a self-assessment and receive educational content, followed by a post-test. The results showed a notable increase in knowledge scores, with the average pre-test score at 4.61 improving to 6.48 post-intervention. Minimum scores increased from 1 to 4, and maximum scores from 8 to 9. These findings suggest that the ‘Ibu Peri Cerita’ application is effective in increasing oral health literacy among pregnant women. The improvement in awareness is expected to support better prenatal health outcomes and contribute to reducing the risk of low birth weight and stunting.